The effect of corporate governance on transparency and performance of Malaysian companies / Mohd Hassan Che Haat - Che Haat, Mohd Hassan (2006)
Ideally, high corporate governance standards have been linked to higher firm performance. An effective governance framework should strike a balance between conformance and performance. Hence, the current study attempts to examine the adequacy of reporting and corporate governance practices by using corporate governance reporting score. In addition, it also attempts to find out whether good corporate governance practices have a positive relationship with corporate transparency and performance. Apart from developing a Malaysian-based corporate governance reporting score, this study attempts to compare corporate governance practices in companies with good financial performance and those with relatively SV-destroying. The sample consists of 145 companies, 73 companies selected by KPMG/The Edge Award (Lee, 2003), which are considered to have S V-enhancing in terms of shareholder value creation and used as a benchmark to evaluate the rest of companies listed on Bursa Malaysia. The other group consists of 73 non-award achievers which represent SV-destroying companies. Studying corporate governance practices of these two groups of companies would help understand the importance of this issue in improving timeliness of reporting and the extent of disclosures, which in turn should positively affect a company's market performance. This should be the case for comparable companies that have improved business performances. The results of the survey reveal that there is much room for improvement vis-a-vis Malaysian companies reporting of their practices, as the Mean CG reporting score of these sample firms only came up to 51.3 percent. Comparing between good and SVdestroying companies, in general SV-enhancing companies disclose more but the difference is very marginal and statistically insignificant. Furthermore, the overall findings reveal that CG reporting has been found lacking mainly in areas such as Strategic Planning and Performance Management, Risk Management and Internal Control, Accountability and Transparency, Business Ethics and Responsibility, and Intellectual Capital. It was found that corporate governance factors have a strong predicting power on company performance, mainly due to debt monitoring and foreign ownership. However, there is a significant negative relation between audit quality and performance. When testing the hypotheses whether the high performance is due to better disclosure and timely reporting, the results found that performance is not associated with the level of disclosure and timely reporting. The results indicate that disclosure and timeliness are not significant contributing factors in the relationship between corporate governance and market performance and therefore the findings do not support signalling theory. In general, the findings raise the issue of ineffectiveness of monitoring power by Malaysian corporate governance standards to directors and insiders as well as the usefulness of financial report itself.